Intra-Abdominal Actinomycosis Mimicking Malignant Abdominal Disease - Ridha, Ali (Case Rep Infect Dis, 2017)
Abdominal actinomycosis is a rare infectious disease, caused by gram positive anaerobic bacteria, that may appear as an abdominal mass and/or abscess (Wagenlehner et al. 2003). This paper presents an unusual case of a hemodynamically stable 80-year-old man who presented to the emergency department with 4 weeks of worsening abdominal pain and swelling. He also complains of a 20-bound weight loss in 2 months. A large tender palpable mass in the right upper quadrant was noted on physical exam. Laboratory studies showed a normal white blood cell count, slightly decreased hemoglobin and hematocrit, and mildly elevated total bilirubin and alkaline phosphatase. A CT with contrast was done and showed a liver mass. Radiology and general surgery suspected malignancy and recommended CT guided biopsy. The sample revealed abundant neutrophils and gram positive rods. Cytology was negative for malignancy and cultures eventually grew actinomyces. High dose IV penicillin therapy was given for 4 weeks and with appropriate response transitioned to oral antibiotic for 9 months with complete resolution of symptoms.